2015
DOI: 10.1002/rcm.7165
|View full text |Cite
|
Sign up to set email alerts
|

Identification of alkaloid constituents from Fangchi species using pH control liquid‐liquid extraction and liquid chromatography coupled to quadrupole time‐of‐flight mass spectrometry

Abstract: The chemical profiling of alkaloids in F. species with different origins was performed for the first time and provided diagnostic ions for diverse alkaloids in F. species. Marker compounds were suggested based on the 28 characterized compounds for quality evaluation and the differentiation of Fangchi species with four different origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 37 publications
4
36
0
Order By: Relevance
“…As shown in Figure B, the use of moderately acidic additives improved the chromatographic properties when compared to ammonium formate alone. The use of 0.05% formic acid together with the addition of 2.5 mM ammonium formate improved the chromatographic resolution and detection sensitivity of the alkaloids (Figure C), which agrees well with the literature .…”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure B, the use of moderately acidic additives improved the chromatographic properties when compared to ammonium formate alone. The use of 0.05% formic acid together with the addition of 2.5 mM ammonium formate improved the chromatographic resolution and detection sensitivity of the alkaloids (Figure C), which agrees well with the literature .…”
Section: Resultssupporting
confidence: 90%
“…Compound 15 showed an abundant [M + H] + ion at m/z 607.2779. The MS/MS spectrum of it was consistent with that of cepharanthine in the literature (Sim et al , ), and the results showed a dimeric isoquinoline fragment at m/z 380.1709 and its demethylated ion at m/z 365.1439, single isoquinoline fragments at m/z 192.1005 and 190.0851 and a diphenyl ether moiety at m/z 227.1058. Other fragments at m/z 576.2396 and 564.2350, which were formed by the losses of NH 2 CH 3 and C 2 H 5 N from the [M + H] + ion, respectively, were also observed.…”
Section: Resultsmentioning
confidence: 99%
“…Both of the ions at m/z 297.1126 and 237.0915 could further eliminate the peripheral groups including CH 3 , OCH 3 and H 2 O. The ions discussed earlier followed the general rules in the literature (Stévigny et al , ; Sim et al , ). Another parallel pathway observed was loss of CH 3 N = CH 2 ( m/z 299.1293) followed by eliminations of the peripheral groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations